2016
DOI: 10.1103/physrevb.93.195208
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental gap of molecular crystals via constrained density functional theory

Abstract: The energy gap of a molecular crystal is one of the most important properties since it determines the crystal charge transport when the material is utilized in electronic devices. This is, however, a quantity difficult to calculate and standard theoretical approaches based on density functional theory (DFT) have proven unable to provide accurate estimates. In fact, besides the well-known band-gap problem, DFT completely fails in capturing the fundamental gap reduction occurring when molecules are packed in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 63 publications
(84 reference statements)
1
13
0
Order By: Relevance
“…The most widely encountered of these is the many-electron self-interaction error (SIE) 6 , or delocalization 12 error, which is manifested as a spurious curvature in the total-energy profile of a system with respect to its total electron number 13 . The SIE contributes to inaccuracies in insulating band gaps 14 , charge-transfer energies 15,16 , activation barriers 17 , binding and formation energies, as well as in spin-densities and their moments. While the nature of SIE is well understood, it remains persistently challenging to reliably avoid its introduction using approximate xc functionals of a computationally tractable, explicit analytical form, even if exact exchange is incorporated (see, e.g., the B3LYP curve in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The most widely encountered of these is the many-electron self-interaction error (SIE) 6 , or delocalization 12 error, which is manifested as a spurious curvature in the total-energy profile of a system with respect to its total electron number 13 . The SIE contributes to inaccuracies in insulating band gaps 14 , charge-transfer energies 15,16 , activation barriers 17 , binding and formation energies, as well as in spin-densities and their moments. While the nature of SIE is well understood, it remains persistently challenging to reliably avoid its introduction using approximate xc functionals of a computationally tractable, explicit analytical form, even if exact exchange is incorporated (see, e.g., the B3LYP curve in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Table IV Putting molecules in a solvent, for example in molecular crystal, gap renormalizes due to electronic polarization effects. [53][54][55] Within the non-local vdW-DF-cx functional, the relaxed lattice parameters of TCNQ crystal are: a=8. Fig.…”
Section: First-principles Dft and Gw Calculationsmentioning
confidence: 99%
“…Because of that, we also use constrained-DFT (c-DFT) [44][45][46][47] with the local spin density approximation for the exchange correlation potential as a complementary approach. In fact it has been demonstrated that c-DFT generally returns quite accurate results for the energies of the frontier orbitals of molecules inside crystals and clusters 48,49 . Specifically, the energy of the lowest unoccupied molecular orbital (LUMO) of Alq The G 0 W 0 DOS is presented in Fig.…”
Section: A Electronic Propertiesmentioning
confidence: 99%